THE INFLUENCE OF BRAND AMBASSADOR AND SHOPPING LIFESTYLE ON PURCHASE DECISION MEDIATED BY BRAND AWARENESS ON SCARLETT WHITENING - Devi Shilvinabe; Nurul Komariyatin (Majapahit Journal of Islamic Finance and Management, 2026)
The Indonesian beauty industry is growing rapidly as people's attention to appearance increases. This study aims to analyze the influence of brand ambassadors and shopping lifestyle on purchase decisions with brand awareness as a mediating variable for Scarlett Whitening products. A quantitative method was used by distributing questionnaires to 150 respondents aged 15–35 years in Jepara Regency and analyzed using SmartPLS 4. The results showed that brand ambassadors and shopping lifestyle had a positive and significant effect on purchase decisions, with shopping lifestyle as the most dominant factor. Brand awareness was proven to be able to mediate the influence of both variables on purchase decisions. These findings emphasize the importance of marketing strategies that align with consumer lifestyles, selecting the right brand ambassadors, and strengthening brand awareness to increase Scarlett Whitening purchase decisions.